FACULTY E-RESOURCES USE: A COMPARATIVE STUDY - Bipin Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The library is always regarded as the organization's information hub, regardless of the type of organisation. The fulfilment of the requirements of the library's patrons is the primary function of the library. Libraries, regardless of whether they are academic, public, school, or special, are institutions that serve their patrons by providing a variety of services and facilities. The provision of informational services to patrons is one of the primary functions of libraries, which are viewed as service institutions. As such, library activities are geared toward meeting the requirements of patrons; this is because, in a service centre, the satisfaction of customers is the primary focus. The quality of the services and amenities provided to users has the greatest impact on the degree to which they are satisfied with their experience and can assist users with educational processes.